Randall Jarrell and his age - Burt, Stephanie, 1971- (Columbia University Press, 2002)
Randall Jarrell (1914-1965) was the most influential poetry critic of his generation. He was also a lyric poet, comic novelist, translator, children's book author, and close friend of Elizabeth Bishop, Robert Lowell, Hannah Arendt, and many other important writers of his time. Jarrell won the 1960 National Book Award for poetry and served as poetry consultant to the Library of Congress. Amid the resurgence of interest in Randall Jarrell, Stephen Burt offers this brilliant analysis of the poet and essayist. Burt's book examines all of Jarrell's work, incorporating new research based on previously undiscovered essays and poems. Other books have examined Jarrell's poetry in biographical or formal terms, but none have considered both his aesthetic choices and their social contexts. Beginning with an overview of Jarrell's life and loves, Burt argues that Jarrell's poetry responded to the political questions of the 1930s, the anxieties and social constraints of wartime America, and the apparent prosperity, domestic ideals, and professional ideology that characterized the 1950s. Jarrell's work is peopled by helpless soldiers, anxious suburban children, trapped housewives, and lonely consumers. Randall Jarrell and His Age situates the poet-critic among his peers--including Bishop, Lowell, and Arendt--in literature and cultural criticism. Burt considers the ways in which Jarrell's efforts and achievements encompassed the concerns of his time, from teen culture to World War II to the Cuban Missile Crisis; the book asks, too, how those efforts might speak to us now.--